Az afrikai lantok története és típusai - Brauer-Benke, József (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
The historical survey presented here demonstrates that musical instruments of the lute type derive from outside the African continent, even though they have probably been present in the North African region for several millennia. The first evidence of their appearance in ancient Egypt goes back to the era of Dynasty XVIII (ca. 1550–1292 BCE). The use of lutes having a long neck may have been preserved later among various Berber-speaking populations, and their wide dissemination over West Africa can only be dated with certainty to the period after the 14th century, when widespread conversion to Islam led to the replacement of an older arched type (having few strings and capable of producing a limited range of sounds) with a long-necked lute type borrowed from the Berbers, which can be considered more advanced owing to its mode of stretching the strings with a tuning ring. This paradigm shift is obvious in the epic song cycle known as Gassire’s Lute. Parallel to this development harp lutes appeared as a kind of cross between lutes and bow harps; and types of this new instrument having a larger body and multiple strings could rival the short-necked oud, an urban instrument spread by Arab tribes. Perhaps for this reason, the latter was not widely adopted among the Islamized populations of West Africa, while it did become popular in Europe in the 13th century, first adopted by the Spaniards. The fact that long-necked lutes are found only in North and West Africa also proves that the Nilotic-speaking peoples did not borrow these, unlike harps and lyras, which they did. Had they done so, the southward expansion of Nilotic-speaking populations would have led to the distribution of long-necked lutes over Central and Eastern Africa. For the same reason these instruments must have appeared in West Africa only after the Bantu expansion, before which era their use must have been restricted to Berber-speaking groups for three millennia. Short-necked lutes are likely to have been originated in Central Asia and they certainly spread from that region; the archaic type that is carved from one block of wood and has a bottle-like shape spread to Southeast Asia with the Muslim expansion and may have been carried from there to the islands of the Indian Ocean and sporadically to East Africa as well. Its wider adoption over the latter region was probably hindered by the ubiquity of rival instruments (harps and lyras) there. Moreover, the short-necked lutes carved of a single block of wood were not suitable for further development with the aim of increasing the volume, hence the recent widespread adoption among the inhabitants of the eastern and southern regions of Africa of a long-necked lute type having a larger, box-like body.